Banana peels as potential prebiotic and functional ingredient - Tan, Chee Yee; Mohd Arifin, Nurul Nadiah; Sabran, Mohd Redzwan (Jurnal Gizi dan Pangan/Journal of Nutrition and Food, 2024)
This study aims to determine the prebiotic potential of the banana peel on the growth of probiotic Lactobacillus spp. in vitro and to utilize the peel as a functional ingredient in preparing biscuits. Peels of dessert banana (pisang berangan) and plantain (pisang nangka) were oven-dried and homogenized, and the total sugar content was determined. Subsequently, different cultivation media were made by substituting the carbon source with Banana Peel Powder (BPP), Plantain Peel Powder (PPP), glucose, and inulin. These media were later fermented with probiotic Lactobacillus spp., extracted from a probiotic drink. The growth performance was accessed following 24 hours of incubation. BPP and PPP were incorporated into the preparation of biscuits as functional ingredients. A portion of wheat flour was substituted with 10%, 20%, and 30% of BPP and PPP, respectively, during the preparation of the biscuits. These biscuits were then analyzed for proximate composition, physical properties, and estimated Glycaemic Index (eGI). The supplementation of BPP and PPP in the media improved the probiotic bacteria's growth rate and generation time as the media had a significantly higher amount of Lactobacillus spp. compared to others. Both BPP- and PPP-supplemented media had significantly low pH, indicating intense metabolic activity of the bacteria utilizing the peels. Results also showed significant differences in the total dietary fiber and protein content of BBP- and PPP-incorporated biscuits. The addition of BPP and PPP did not significantly affect the physical properties of the biscuit, and such incorporation resulted in lower eGI when compared to the control. BPP and PPP possess potential prebiotic properties and can be utilized as functional ingredients. Further study is warranted to explore other prebiotic properties of banana peels and to investigate consumers' acceptance of banana peel-incorporated foods.